Hypothermic Oxygenated Perfusion Versus Normothermic Regional Perfusion in Liver Transplantation From Controlled Donation After Circulatory Death: First International Comparative Study. Issue 5 (November 2020) - Muller, Xavier; Mohkam, Kayvan; Mueller, Matteo; Schlegel, Andrea; Dondero, Federica; Sepulveda, Ailton; Savier, Eric; Scatton, Olivier; Bucur, Petru; Salame, Ephrem; Jeddou, Heithem; Sulpice, Laurent; et al.
Abstract : Objective: To compare HOPE and NRP in liver transplantation from cDCD. Summary of Background Data: Liver transplantation after cDCD is associated with higher rates of graft loss. Dynamic preservation strategies such as NRP and HOPE may offer safer use of cDCD grafts. Methods: Retrospective comparative cohort study assessing outcomes after cDCD liver transplantation in 1 Swiss (HOPE) and 6 French (NRP) centers. The primary endpoint was 1-year tumor-death censored graft and patient survival. Results: A total of 132 and 93 liver grafts were transplanted after NRP and HOPE, respectively. NRP grafts were procured from younger donors (50 vs 61 years, P < 0.001), with shorter functional donor warm ischemia (22 vs 31 minutes, P < 0.001) and a lower overall predicted risk for graft loss (UK-DCD-risk score 6 vs 9 points, P < 0.001). One-year tumor-death censored graft and patient survival was 93% versus 86% ( P = 0.125) and 95% versus 93% ( P = 0.482) after NRP and HOPE, respectively. No differences in non-anastomotic biliary strictures, primary nonfunction and hepatic artery thrombosis were observed in the total cohort and in 32 vs. 32 propensity score-matched recipients Conclusion: NRP and HOPE in cDCD achieved similar post-transplant recipient and graft survival rates exceeding 85% and comparable to the benchmark values observed in standard DBD liver transplantation. Grafts in the HOPE cohort were procured from older donors and had longer warm ischemia times, and consequently achieved higher utilization rates. Therefore, randomized controlled trials with intention-to-treat analysis are needed to further compare both preservation strategies, especially for high-risk donor-recipient combinations. Abstract : Supplemental Digital Content is available in the text